Proximal composition, caloric value and price-nutrients correlation of comercial cuts of tambaqui (Colossoma macropomum) and pirarucu (Arapaima gigas) in diferente body weight classes (Amazon: Brazil) (Research, Society and Development, 2021)
The aimed of the study was to evaluate the caloric value as a function of the proximal composition and correlate the selling price with the nutritional values ​​of commercial cuts of tambaqui (Colossoma macropomum) and pirarucu (Arapaima gigas) in different weight classes. The sample collections were performed in two processing units located in the state of Rondônia, Brazil. Were 200 tambaquis in five weight classes were studied. And, were 77 pirarucus were studied in seven weight classes. The design was completely randomized, with processing carried out in triplicate. The Kruskal-Wallis test (α=0.05) was used to compare the averages and the Spearman correlation (ρ) between price and nutrients. The commercial cuts with the highest caloric value were the tambaqui filet (145.70 kcal/100g) and the pirarucu filet mignon (119.11 kcal/100g) (p